2020
DOI: 10.1016/j.foodres.2020.109491
|View full text |Cite
|
Sign up to set email alerts
|

Aroma-retention capacities of functional whey protein aggregates: Study of a strawberry aroma in solutions and in fat-free yogurts

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Furthermore, they explained the differences in the release of various aroma compounds with the conformational state of proteins, since they used a native whey protein isolate and two types of MWP, one with a relatively small particle size (200 nm) and one with a polydisperse MWP (200 and 1000 nm). In addition, they used MWP in fat-free yogurts and found a decreased release of hydrophobic aroma compounds in particular, such as nonan-2one, and attributed this to hydrophobic interactions of aroma compounds with proteins [96]. This suggests that in the present work, both high viscosity and interactions were responsible for the lower aroma release from the MWP sample.…”
Section: Aroma Releasementioning
confidence: 55%
See 1 more Smart Citation
“…Furthermore, they explained the differences in the release of various aroma compounds with the conformational state of proteins, since they used a native whey protein isolate and two types of MWP, one with a relatively small particle size (200 nm) and one with a polydisperse MWP (200 and 1000 nm). In addition, they used MWP in fat-free yogurts and found a decreased release of hydrophobic aroma compounds in particular, such as nonan-2one, and attributed this to hydrophobic interactions of aroma compounds with proteins [96]. This suggests that in the present work, both high viscosity and interactions were responsible for the lower aroma release from the MWP sample.…”
Section: Aroma Releasementioning
confidence: 55%
“…All aroma compounds exhibited a decreased aroma release from the MWP sample compared to the Wat sample, which could be linked to the significantly higher viscosity of the MWP sample or the binding of aroma compounds by proteins, both resulting in a slower diffusion of aroma compounds in the emulsion. Lesme et al [96] also found a decreased aroma release for MWP compared to water, which, according to them, was due to the aroma-binding ability of proteins. Furthermore, they explained the differences in the release of various aroma compounds with the conformational state of proteins, since they used a native whey protein isolate and two types of MWP, one with a relatively small particle size (200 nm) and one with a polydisperse MWP (200 and 1000 nm).…”
Section: Aroma Releasementioning
confidence: 91%
“…Methyl ketones can be produced by lipid autoxidation and microbial metabolism 30 . The protein denaturation may decrease the binding affinity of 2‐nonanone, 31 leading to a reduction in its concentration in EWP. Styrene can cause offensive odorants in scrambled egg 32 .…”
Section: Resultsmentioning
confidence: 99%
“…A negative value of R indicates a salting‐out effect, increasing the release rate of fragrance compounds. Conversely, a positive value of R translates the occurrence of interactions between fragrance and emulsion ingredients, limiting fragrance release [52].…”
Section: Dermocosmetic Emulsions and Fragrancementioning
confidence: 99%